2012
DOI: 10.1177/0042085912445643
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Efficacy of Different Types of Parental Involvement Programs for Urban Students

Abstract: This meta-analysis of 51 studies examines the relationship between various kinds of parental involvement programs and the academic achievement of pre-kindergarten-12th-grade school children. Analyses determined the effect sizes for various parental involvement programs overall and subcategories of involvement. Results indicate a significant relationship between parental involvement programs overall and academic achievement, both for younger (preelementary and elementary school) and older (secondary school) stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
340
2
50

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(410 citation statements)
references
References 39 publications
18
340
2
50
Order By: Relevance
“…Parent focus group responses also revealed that the creation of a parent group, combined with ILPs' increased leadership status within the school, meant parents felt more confidence both that their concerns and suggestions regarding classroom practice would be addressed, and in their own abilities to provide their children with literacy support. This is consistent with other research findings (Bolivar & Chrispeels, 2011;Jeynes, 2012;Mutch & Collins, 2012;Scanlan, 2011;Tilley-Lubbs, 2011) that demonstrate the positive influence parent groups have on increasing parents' ability, confidence, and willingness to collaborate with school staff. Responses of the parent group also revealed that even small gestures such as the "meet and greet sessions" before and after school first instigated by the ILPs and then followed up by the principal and individual teachers, were reported to have a positive influence over attendance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Parent focus group responses also revealed that the creation of a parent group, combined with ILPs' increased leadership status within the school, meant parents felt more confidence both that their concerns and suggestions regarding classroom practice would be addressed, and in their own abilities to provide their children with literacy support. This is consistent with other research findings (Bolivar & Chrispeels, 2011;Jeynes, 2012;Mutch & Collins, 2012;Scanlan, 2011;Tilley-Lubbs, 2011) that demonstrate the positive influence parent groups have on increasing parents' ability, confidence, and willingness to collaborate with school staff. Responses of the parent group also revealed that even small gestures such as the "meet and greet sessions" before and after school first instigated by the ILPs and then followed up by the principal and individual teachers, were reported to have a positive influence over attendance.…”
Section: Discussionsupporting
confidence: 91%
“…Current research also indicates that parent-school partnerships can have a positive influence upon students' learning outcomes (Jeynes, 2012). Establishing meaningful partnerships between communities and schools takes time and effort (Mutch & Collins, 2012;deFur, 2012).…”
mentioning
confidence: 99%
“…It is widely believed that parents' involvement in their children's academic life has positive effects on children's academic achievement. Therefore, it is not surprising that the promotion of parental involvement has featured prominently in educational policies in recent years (No Child Left Behind Act of 2001 and that a number of meta-analyses have been published in the last decade showing that parental involvement may indeed have positive effects on children's academic development (Fan & Chen, 2001;Hill & Tyson, 2009;Jeynes, 2003Jeynes, , 2005Jeynes, , 2007Jeynes, , 2012. However, despite the number of studies on parental involvement, there is still no clear consensus of how strong its effects are and whether parental involvement is always a good thing (Pomerantz, Moorman, & Litwack, 2007).…”
mentioning
confidence: 99%
“…Este resultado da cuenta de que los procesos educativos que se llevan a cabo dentro de la escuela y el aula aún no forman parte del ámbito de acción directo de los apoderados. Jeynes (2012) sugiere, sin embargo, que la participación de los padres, madres y apoderados en las actividades de la escuela tiene un mayor efecto sobre los resultados escolares de la infancia en la medida que son pedagógicamente intencionadas por parte de los directivos y docentes de los establecimientos educacionales. Sin dirección se correría el riesgo de que las prácticas de involucramiento parental en el hogar o en la escuela no produzcan el impacto deseado en los propósitos de aprendizaje esperados por la escuela para sus estudiantes.…”
Section: Discussionunclassified